ECONOMIC ANALYSIS OF LAW TERHADAP PEMIDANAAN INSIDER TRADING DALAM PROSES MERGER SEBAGAI KEJAHATAN KORPORASI - Sudwijayanti, Sudwijayanti (DiH: Jurnal Ilmu Hukum, 2017)
Corporate crime is one of the crimes that arise with the advanced of economic, technological and trade liberalization activities. The problems with non-conventional crimes are due to the difficulty of clearly determining the victims and the difficulty of criminal prosecution of perpetrators. Corporate liability is also not well known in Indonesian criminal law, due to the very strong influence of the principle of sociates delinquere non-potest. One of the capital market crimes that may occur as a corporate crime is insider trading. Insider trading defined as securities trading transactions conducted by insiders by utilizing insider information that has not been published. Information on the merger as a form of corporate restructuring categorized as material facts. Merger is a legal act of one or more Companies to merge with another Company into one of existing company. In case that insider trading takes place in the merger process by the corporation, difficulty of verification for punishment will be complicated, considering the legal vacuum to convict that crime. Prosecution towards corporations, eventhough closely related to financial matters, but also intersect with purposes and functions, i.e. the protection of society and the individual offenders. Based on that purpose, Economic Analysis of Law expected to answer the legal vacuum and determine the important aspects of proper legal practice, so that a specific and appropriate punishment can be found for the offense. Considering not all penalties can be imposed on corporation. Hopefully, Economic Analysis of Law able to provide solutions for Indonesia modern criminalization.